(untitled) (Human Resource Strategy and Practice, 2025)
This ongoing research examines the universal yet frequently overlooked phenomenon of workplace ethnic discrimination in Ghana, a determinant of organizational performance. It analyzes the influence of workplace discrimination based on ethnicity on Ghana’s operational efficiency in the manufacturing industry, with a novel focus on psychological health as a mediator and self-esteem as a moderator. Theories like Social Identity Theory and Conservation of Resources are combined to examine the interaction among group identification, dynamic resource distribution, and workplace discrimination. The study analyzed survey data from 400 manufacturing employees in Accra using regression-based mediation and moderation modeling. Key findings reveal three significant contributions: (1) ethnic discrimination directly impacts workplace productivity (β = −0.300, p ˂ 0.01); (2) psychological health partially mediates this relationship, explaining how discrimination harms productivity through employee psychological health (indirect effect = −0.244, p ˂ 0.005); and (3) self-esteem buffers the negative impact on psychological health (interaction β = 0.028, p ˂ 0.05), with high self-esteem employees showing greater resilience. These findings advance theoretical understanding by integrating identity-threat and resource-conservation mechanisms in a non-Western context. Practically, they show that manufacturing firms must move beyond symbolic diversity commitments to implement concrete reforms such as transparent promotion systems, inclusive leadership development, and workplace mental health support to protect both employees’ well-being and organizational productivity. The study highlights the strategic importance of inclusive human resource practices, psychological health support, and an equitable promotion system for sustainable productivity in an ethnically diverse workplace.